Shaping Healthier Societies and Building Higher Performing Health Systems in the GCC Countries - World Bank Group (Washington, DC, 2015)
This policy note summarizes the central health sector trends and challenges in the Gulf Cooperation Council (GCC) countries of the Middle East and North Africa region (MENA). These countries are Saudi Arabia, Kuwait, Bahrain, the United Arab Emirates (UAE), Oman, and Qatar. The note also provides an overview of the GCC country context, discussing the commonalities between the six member states, and the major areas of engagement by the health, nutrition, and population (HNP) global practice of the World Bank in support of the health sector reform priorities of these countries. The areas of engagement focus on three main clusters of work: (i) developing multi-layered solutions for improving non-communicable disease and road safety outcomes; (ii) health system strengthening; and (iii) integrating health policy solutions within the wider institutional and policy frameworks in the GCC countries. The note builds on an earlier HNP regional strategy prepared by the World Bank in 2013 focusing on the concepts of fairness and accountability. The strategy highlighted the importance of improvements in health system performance in MENA countries from an equity, accountability, and fiscal sustainability perspective. The framework of the strategy covers equity in health status, financial protection and responsiveness, and the accountability of populations, payers, and health service providers interacting within the health system.